Seed source variation in the seed and seedling characters of ashoka (saraca asoca (Roxb.) de wilde) - Deepa K S (Department of Tree physiology and Breeding, College of Forestry, 2010)
An investigation was conducted on “Seed source variation in the seed and seedling characters of ashoka [Saraca asoca (Roxb.) de Wilde]” in the nursery of College of Forestry, Kerala Agricultural University, Thrissur, Kerala, India. In order to fix the seed sources, the state was divided into six equal portions based on the latitude. The seeds collected from each source were bulked and used for the study. Seed traits, germination attributes and seedling characters were used for investigating seed source variation in Saraca asoca. Different seed traits like seed length, seed breadth, seed length to breadth ratio, seed weight and pericarp thickness was evaluated in the present investigation. Study showed significantly lower size for the seeds collected from seed source SS 3. The performance of seed source SS 1, SS 2, SS 4 and SS 6, were on par with each other in case of most of the seed attributes.